2020
DOI: 10.1177/1747021820935457
|View full text |Cite
|
Sign up to set email alerts
|

Literacy skill and intra-individual variability in eye-fixation durations during reading: Evidence from a diverse community-based adult sample

Abstract: To understand the effects of literacy on fundamental processes involved in reading, we report a secondary data analysis examining individual differences in global eye-movement measures and first-pass eye-movement distributions in a diverse sample of community-dwelling adults aged 16 to 64. Participants ( n = 80) completed an assessment battery probing verbal and non-verbal cognitive abilities and read simple two-sentence passages while their eye movements were recorded. Analyses were focused on charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
(203 reference statements)
0
7
0
Order By: Relevance
“…Few studies have investigated reading multi-sentence texts (but see Payne & Stine-Morrow, 2012; Stine-Morrow et al, 2010; Whitford & Titone, 2017, 2019) although it will be important to assess whether effects in studies reviewed here, which principally concern the reading of sentences displayed across a single line, generalize to more typical reading situations. Similarly, few studies have investigated reading in middle-aged participants (but see Payne et al, 2020; Steen-Baker et al, 2017; Warrington et al, 2018), and to our knowledge, no studies have examined aging effects separately for young-old adults (60–69 years) and older-old adults (80+ years), who may have distinct cognitive profiles (Smith & Bates, 1993). Such studies will nevertheless be crucial for obtaining a detailed understanding of the changes that take place in cognitive and oculomotor mechanisms across the adult lifespan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have investigated reading multi-sentence texts (but see Payne & Stine-Morrow, 2012; Stine-Morrow et al, 2010; Whitford & Titone, 2017, 2019) although it will be important to assess whether effects in studies reviewed here, which principally concern the reading of sentences displayed across a single line, generalize to more typical reading situations. Similarly, few studies have investigated reading in middle-aged participants (but see Payne et al, 2020; Steen-Baker et al, 2017; Warrington et al, 2018), and to our knowledge, no studies have examined aging effects separately for young-old adults (60–69 years) and older-old adults (80+ years), who may have distinct cognitive profiles (Smith & Bates, 1993). Such studies will nevertheless be crucial for obtaining a detailed understanding of the changes that take place in cognitive and oculomotor mechanisms across the adult lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…This slower processing might be a consequence of cognitive decline. Alternatively, it may be because growth in the mental lexicon from a lifetime of exposure to written language can slow access to specific lexical items (e.g., Blanco et al, 2016; Ramscar et al, 2014) or because of increased competition from orthographic neighbors in older readers (Payne et al, 2020). Moreover, the direction of the effect is also unclear.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, we found no evidence for effects on word-level processes. High-verbal readers ( Stine-Morrow et al, 2008 ) and those with higher levels of reading proficiency ( Landi, 2010 ; Ng et al, 2020 ; Payne et al, 2020 ) and print exposure ( Payne et al, 2012a ) do show facilitated lexical processing. However, this advantage likely arises from extensive exposure to lexical items in diverse contexts.…”
Section: Discussionmentioning
confidence: 99%
“…However, this advantage likely arises from extensive exposure to lexical items in diverse contexts. For example, among proficient readers, word reading times are sensitive to orthographic and phonological neighborhoods ( Payne et al, 2020 ), suggesting that skilled reading is supported by a complex lexical network of semantic and surface features. As such, 8 weeks of reading may be insufficient to measurably enhance lexical recognition processes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regulation of attention again seems to play an important role. Payne, Federmeier, and Stine-Morrow (2020) found that eye-movement patterns among poorer readers showed a higher proportion of very slow fixation times that were not driven by properties (e.g., length or frequency) of the words themselves—a pattern suggestive of attentional lapses. In addition, like production, successful prediction has been linked to prestimulus alpha-power decreases in EEG activity (Rommers, Dickson, Norton, Wlotko, & Federmeier, 2017), again highlighting the necessity of regulation of information flow.…”
Section: Predicting and Adaptingmentioning
confidence: 90%